Pap smear awareness, utilization, and pattern of cervical intraepithelial neoplasia among women attending a tertiary hospital in Northwestern Nigeria - Abdulrahman Shuaibu; Bukar Alhaji Grema; Godpower Chinedu Michael (Muller Journal of Medical Sciences and Research, 2018)
Background: Globally, cervical cancer affects approximately 528,000 women each year, with about 80% of them occurring in developing countries. Developed countries have successfully reduced the incidence of cervical cancer by 70% through organized cervical screening programs. Objective: The aim of the study is to assess the level of Pap smear awareness and utilization among adult females attending the general outpatient clinic of Aminu Kano Teaching Hospital, Northwestern Nigeria, in order to encourage early detection of premalignant cervical cancer. Methods: This was a descriptive cross-sectional study that assessed Pap smear awareness, utilization, and pattern of cervical intraepithelial neoplasia among 422 adult females in Kano, Northwestern Nigeria, using an interviewer-administered questionnaire. SPSS version 20 was used to analyze the data. The sociodemographic characteristics of participants, risk factors of cervical cancer, and awareness and utilization of Pap smears by participants were expressed in means and proportions. The Chi-square test was used to explore associations between categorical variables. Logistic regression was performed to identify the predictors of Pap smear awareness and its utilization among the study participants. P < 0.05 was considered statistically significant. Results: Of the 422 women who participated in the study, the majority (292, 69.2%) had never heard of Pap smear screening while 130 (30.8%) were aware of Pap smear. Similarly, 342 (81.0%) women who participated in the study had never undergone a Pap smear. Three hundred and eight (74%) had normal cytology results, 107 (25%) had inflammatory changes, 4 (0.8%) had low-grade squamous intraepithelial lesion, and 1 (0.2%) had high-grade squamous intraepithelial lesion. Having higher education and being employed were associated with Pap smear awareness while increasing age and educational level were associated with Pap smear utilization. Conclusion: This study revealed a low awareness and utilization of Pap smear screening in Northwestern Nigeria.